THE INFLUENCE OF PRICE, SERVICE QUALITY AND CUSTOMER SATISFACTION ON CUSTOMER LOYALTY OF PT. PUTRA PELANGI PERKASA TAJUR BOGOR - Hanipah, Imanda; Ismartaya, Ismartaya; Silaningsih, Endang (Universitas Nusa Cendana, 2025)
This study aimed to investigate the influence of customer satisfaction, service quality, and price on customer loyalty. This quantitative study surveyed one hundred people with a non-probability sample procedure grounded in purposive sampling. This study discovered a significant positive correlation between competitive price, high-quality service, and customer satisfaction and consumer loyalty. To optimize profit amidst competitive market dynamics, enhance customer loyalty, and successfully manage risk, firms must possess a comprehensive understanding of these three factors, as concluded. Keywords: Price; Service Quality; Customer Satisfaction; Customer Loyalty